Peran Pengungkapan Corporate Social Responsibility dalam Memediasi Hubungan Koneksi Politik dengan Kemungkinan Kecurangan Laporan Keuangan - Hady, Anindya Ratna Kartika; Chariri, Anis (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p18, 2022)
The purpose of the study was to examine the relationship between political affiliation and the potential for misleading financial statements, as well as the function of corporate social responsibility disclosure in reducing its effect on public companies that issue sustainability reports in 2019 and 2020. Sampling used purposive sampling to obtain data from 138 companies. publicly traded on the Indonesia Stock Exchange. In conducting the analysis used path analysis. The results show that financial statement fraud is negatively affected by political connections according to the regression test that has been carried out. This study also shows that CSR disclosure can mediate the relationship of political connections with fraudulent financial reporting. Keywords: CSR Disclosure; Financial Statement Fraud; Political Connections.